Chemistry education students’ perception toward their learning outcomes during online learning - Rizkia, Noviza; Nazmi, Saura Alaifa; Fiana, Lisa Fitri; Reza, Muhammad (Universitas Negeri Malang, 2023)
This study aims to determine the self-perception of chemistry education students related to online learning in the UIN Ar-Raniry. This descriptive research involved chemistry education students of the 2019 batch. Their perception was obtained using an online questionnaire with 15 questions. It can be concluded that implementing the online learning system does not entirely affect students' learning outcomes. REFERENCESAl-Idrus, S. W., Muti’ah, M., & Rahmawati, R. (2021). Analisis Proses Pembelajaran Daring Selama Pandemi Covid-19 pada Mahasiswa Program Studi Pendidikan Kimia FKIP UNRAM. PENSA, 3(1 SE-Articles). https://ejournal.stitpn.ac.id/index.php/pensa/article/view/1246Arisandi, Y., Dasna, I. W., Sumari, S., Habiddin, H., Ibnu, S., & Subandi. (2021). Promoting vocational students' perception and achievement towards Chemistry: SPARE Learning Strategy for students majoring in Automotive Engineering. Turkish Journal of Computer and Mathematics Education (TURCOMAT), 12(13), 6357–6365.Belawati, T. (2019). Pembelajaran Online. Universitas Terbuka.Habiddin, H., Yahmin, Y., Retnosari, R., Muarifin, M., Aziz, A. N., Husniah, I., & Anwar, L. (2020). Chemistry students' attitude towards chemistry. AIP Conference Proceedings, 2215(1), 20005. https://doi.org/10.1063/5.0000496Mandailina, V., Pramita, D., & Haifaturrahmah, H. (2021). Pembelajaran Daring Dalam Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Selama Pandemi Covid-19: Sebuah Meta-Analisis. Indonesian Journal of Educational Science (IJES), 3(2), 120–129.Pratiwi, N. N., & Puspasari, D. (2021). PENGARUH PENGGUNAAN PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA. JAMP : Jurnal Administrasi Dan Manajemen Pendidikan; Vol 4, No 4 (2021): Volume 4 No 4 Desember 2021. https://doi.org/10.17977/um027v4i42021p320Purwanto, A., Pramono, R., Asbari, M., Hyun, C. C., Wijayanti, L. M., Putri, R. S., & Santoso, priyono B. (2020). Studi Eksploratif Dampak Pandemi COVID-19 Terhadap Proses Pembelajaran Online di Sekolah Dasar. EduPsyCouns: Journal of Education, Psychology and Counseling, 2(1), 1–12.Putri, M., & Kurniawati, Y. (2021). Students' learning interest using computer and android in acid base teaching. J-PEK (Jurnal Pembelajaran Kimia), 6(2), 63–71. http://dx.doi.org/10.17977/um026v6i22021p063Putria, H., Maula, L. H., & Uswatun, D. A. (2020). Analisis Proses Pembelajaran dalam Jaringan (DARING) Masa Pandemi Covid- 19 Pada Guru Sekolah Dasar. Jurnal Basicedu, 4(4), 861–872.Riyana, C. (2019). Produksi Bahan Pembelajaran Berbasis Online. Universitas Terbuka.Wardani, S., Haryani, S., Harmiasri, R., & Sari, N. N. (2022). Implementation of Online Learning to Prepare the Youth Generation in the Disruptive Era. J-PEK (Jurnal Pembelajaran Kimia), 7(1), 9–21. https://doi.org/http://dx.doi.org/10.17977/um026v7i12022p009